Тепловий контроль стану різного роду об'єктів - Шматько, О. В.; Бондаренко, І. М. (ХНУРЕ, 2019)
The principle of thermal imaging is described. The possibility of using a pocket thermal imaging device with a matrix IC receiver for effective thermal control of various objects is considered.
Keywords: Тепловий контроль стану різного роду об'єктів